Extant Corpus on Retail Brand Choice Behavior and Multifactor Modelling on its Impact on Malaysia's Retail Stores - Devaraj S. Arujunen; Yeoh Khar Kheng; Amiya Bhaumik (Petra International Journal of Business Studies, 2022)
This study proposed to close the ostensible research gap by examining the impacts of price sensitivity, risk perception, brand awareness, brand experience/brand familiarity, and consumer purchase behaviors on the retail brand choice behavior in Malaysia's retail stores. Moreover, the analysis method will be pivoted to the Smart PLS path modeling technique, which is much more robust and precise. Therefore, this study's proposed research framework was underpinned by Ajzen's Theory of Planned Behavioural and Prospect Theory as well as identifying the most significant factors impacting the retail brand choice behavior in Malaysia's retail stores. The empirical outcomes of this study provide a useful reference in teaching and research for students and faculties who do research or are concerned about retail brand choice behavior issues. In addition, it provides practical guidelines to assist local Malaysian brand retail chain store top management to consider and use the research output in this study to further strengthen their brand management vis-à-vis foreign retail stores in Malaysia. The SEM-PLS results showed that the direct effect of relationships between price consciousness, brand awareness, brand familiarity, risk perception, and consumer purchase behavior was significant and had statistical support for brand choice behavior in Malaysia. As for the moderating effects, consumer purchase behavior as moderator on the relationship between brand awareness, brand familiarity, and consumer brand choice behavior has been statistically established. However, statistical support could not be proved on the moderating effect of consumer purchase behavior on the relationship between price consciousness and risk perception with consumer brand choice behavior in Malaysia's retail stores. The limitations of the study and suggestions for future research were also discussed.